Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1088/1755-1315/272/2/022103
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Robotics Complex for Inspection and Laser Cleaning of Ships from Biofouling

Abstract: The survey of an underwater part of ships is the mandatory procedure by rules of the Russian Maritime Register of Shipping. Periodic cleaning of the ship’s hull from biofouling increases efficiency of its motion. Inspection of the underwater part of the ship during afloat is currently carried out by divers with the underwater video system, devices for non-destructive testing of hull structures, and tools for cleaning surfaces from products of biological fouling and corrosion. The purpose of this study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Remotely operated marine robotics have been developed to remove biofilms and macrofouling from vessel hulls 2,3 (accessed September 12, 2020). Similarly, Kostenko et al (2019) reported on the use of ROVs to inspect and clean vessel submerged surfaces using laser radiation. Remotely operated brush systems are used to remove fouling from finfish farm production nets (e.g., Bloecher and Floerl, 2020).…”
Section: Physical/mechanical Methodsmentioning
confidence: 99%
“…Remotely operated marine robotics have been developed to remove biofilms and macrofouling from vessel hulls 2,3 (accessed September 12, 2020). Similarly, Kostenko et al (2019) reported on the use of ROVs to inspect and clean vessel submerged surfaces using laser radiation. Remotely operated brush systems are used to remove fouling from finfish farm production nets (e.g., Bloecher and Floerl, 2020).…”
Section: Physical/mechanical Methodsmentioning
confidence: 99%
“…Laser technology and its application technology have made great progress in the past 30 years. Laser cleaning technology, which uses the laser radiation scanning the treated hull, has the advantages of faster surface cleaning capability, precise selective processing capability, and better cleaning process control through feedback over rotary brush and high-pressure water cleaning (Fowler 1987 ; Veiko and Shakhno 2002 ; Song et al 2004 ; Chen et al 2010 ; Kostenko et al 2019 ). Laser blasting or cleaning, as shown in Figure 9b , could be introduced commercially in many industrial fields, including underwater ship cleaning.…”
Section: Cleaning Devices and Methodsmentioning
confidence: 99%
“…Chen et al ( 2012 ) developed a cleaning technique for the surface preparation of steel by using a 500-W pulsed high-power fiber laser, as shown in Figure 9a . Kostenko et al ( 2019 ) developed a new underwater cleaning system that consists of an underwater robot and laser cleaning equipment that can be used to clean the hull, as shown in Figure 9d . However, the details of the design of the cleaning laser are not given in the paper.…”
Section: Cleaning Devices and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional hull cleaning is performed by divers. Recently, however, studies have been conducted on cleaning hull surfaces using a remotely operated underwater vehicle (ROUV) [5][6][7][8][9]. A human operator observes the submerged hull surface through a camera mounted on the ROUV and checks its condition.…”
Section: Introductionmentioning
confidence: 99%